Development of Job Instruction on Student Readiness in Carrying out Internship in the Automotive Engineering Skill Competency - Dewi Pujining Nugraheni; Basyirun Basyirun; Eko Supraptono (Universitas Negeri Semarang, 2022)
Abstrak. One of the Ministry of Education and Culture strategies to realize quality and industry-recognized vocational education and training for the Industrial Revolution 4.0 is to provide opportunities for students to carry out industrial work practices or project work with business and industrial world (DU/DI). In practice, vocational students in automotive engineering skill competency tend to be unprepared which results in ineffective internships. This development research aims to formulate the need for job instruction which is oriented toward the readiness of students to carry out an internship program in which there are basic components of instruction and preparation, understanding, testing and participation stages, and follow-up. The readiness of students includes knowledge, skills, and attitudes. Research development uses the ADDIE development model procedure, namely (1) Analysis, (2) Design (3) Development, (4) Implementation, (5) Evaluation. This study aims to: 1) Develop job instruction, 2) Know the feasibility of job instruction, 3) Know the effectiveness of job instructions; 4) Know the increase in student readiness before carrying out internships. The feasibility test obtained a score of 3.63% with a very feasible category. Practicality of 92% with a very practical category. The job instruction that was developed was also tested for its effectiveness with an N-Gain value of 78% which means it is effective and the result is a student readiness level of 84.47% in the ready category. The results of this development research show that job instruction has a positive effect on student readiness and can be used at the stage of industrial work practice debriefing of Automotive Engineering Skill Competency.